Just for now ebook - Glines, Abbi (Sea Breeze, 2012)
An insatiable attraction heats to the boiling point in this steamy book set in the shore town of Sea Breeze from the author of the white-hot The Vincent Boys . Preston is one bad boy. And Amanda has harbored a crush on him for forever. When she finally makes her move on him, it does not end well. But still, she can't resist him. Especially now that he seems to be pursuing her, too. No one wants wants them to be together. Not Amanda's brother Marcus, who is on the verge of his marriage to Low, and definitely not any of Preston's buddies. They know way too much about Preston's dark side. Even Preston realizes he's not good enough for someone like her. But Amanda believes there is more to Preston than his bad boy persona, and she is determined to unearth what he's hiding behind his seductive blue eyes—secrets that could explain his actions. Secrets Amanda might not be able to forgive. Yet the dangerous attraction persists...and neither Preston nor Amanda is going to deny it.